Islamic Multicultural Education for the Prevention of Domestic Violence - Fatha Aulia Riska (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This article aims to explore the concept of anti-violence education within the family and its contribution to strengthening children's character. The study employs a qualitative approach using a literature review method, drawing on data sources including textbooks, online books, prior journal articles related to the research theme, and various other mass media. A harmonious household is realized when the husband demonstrates strong and responsible leadership, the wife exhibits gentleness and affection, and children live in an atmosphere of peace, mutual respect, and love. The family plays a crucial role in shaping a child's character and morals, functioning not merely as a gathering place for father, mother, and children but as a social system with profound influence on child development. Beyond serving as a place of residence, the family constitutes an environment that provides comfort and security for the child. Various dimensions of development including socialization, self-actualization, self-expression, and even deviant behavior may originate and evolve within the family setting.